The relationship between psychosocial hazards and mental health in the construction industry: A meta-analysis. (January 2022) - Sun, Chenjunyan; Hon, Carol K.H.; Way, Kïrsten A.; Jimmieson, Nerina L.; Xia, Bo
Highlights: Mental health issues are a serious concern in the construction industry. A meta-analysis of psychosocial hazards and mental health was conducted. Pooled correlation between psychosocial hazards and mental ill-health was 0.28. High job demands, compared to low job resources, had the greatest adverse impact. Differences across location, occupation, outcome, and timeframe were found. Abstract: The mental health of the construction workforce is an important health and safety concern for the construction industry. Individual studies show that work-related psychosocial hazards have negative implications for mental health. This meta-analysis aims to source and integrate existing studies to ascertain a more holistic indication of the relationship between psychosocial hazards and mental health in the construction industry. By conducting a random-effects meta-analysis, quantitative results of 48 existing studies ( N = 13083), representing 14 identified psychosocial hazards, were combined. Results showed that the pooled correlation coefficient between psychosocial hazards and mental health problems was 0.28 (95% CI 0.24 to 0.33). Among the 14 psychosocial hazards, role conflict ( r = 0.41, 95% CI 0.23 to 0.57) had the strongest significant correlation with mental health problems, followed by role ambiguity ( r = 0.35, 95% CI 0.21 to 0.49), job insecurity ( r = 0.31, 95% CI 0.21 to 0.41), and interpersonal conflict ( r = 0.31, 95% CI 0.25 to 0.36). Meta-regression revealed year of publication effects and subgroup analyses revealed between-study variance could be partially explained by location, occupation, outcome, and timeframe. No publication bias was found according to Egger's test. This study provides a synthesis of the relationship between psychosocial hazards and mental health in the construction industry and highlights implications for future research.